Urinary interleukins (IL)-6 and IL-10 in schoolchildren from an area with low prevalence of Schistosoma haematobium infections in coastal Kenya. - Kariuki H Njaanake; Job Omondi; Irene Mwangi; Walter G Jaoko; Omu Anzala (Public Library of Science (PLoS), 2023)
Urinary cytokines are gaining traction as tools for assessing morbidity in infectious and non-infectious inflammatory diseases of the urogenital tract. However, little is known about the potential of these cytokines in assessing morbidity due to S. haematobium infections. Factors that may influence the urinary cytokine levels as morbidity markers also remain unknown. Therefore the objective of the present study was to assess how urinary interleukins (IL-) 6 and 10 are associated with gender, age, S. haematobium infections, haematuria and urinary tract pathology and; 2) to assess the effects of urine storage temperatures on the cytokines. This was a cross-sectional study in 2018 involving 245 children aged 5-12 years from a S. haematobium endemic area of coastal Kenya. The children were examined for S. haematobium infections, urinary tract morbidity, haematuria and urinary cytokines (IL-6 and IL-10). Urine specimens were also stored at -20°C, 4°C or 25°C for 14 days before being assayed for IL6 and IL-10 using ELISA. The overall prevalence of S. haematobium infections, urinary tract pathology, haematuria, urinary IL-6 and urinary IL-10 were 36.3%, 35.8%, 14.8%, 59.4% and 80.5%, respectively. There were significant associations between prevalence of urinary IL-6, but not IL-10, and age, S. haematobium infection and haematuria (p = 0.045, 0.011 and 0.005, respectively) but not sex or ultrasound-detectable pathology. There were significant differences in IL-6 and IL-10 levels between urine specimens stored at -20°C and those stored at 4°C (p<0.001) and, between those stored at 4°C and those stored at 25°C (p<0.001). Urinary IL-6, but not IL-10, was associated with children's age, S. haematobium infections and haematuria. However, both urinary IL-6 and IL-10 were not associated with urinary tract morbidity. Both IL-6 and IL-10 were sensitive to urine storage temperatures.